Kūkai's transcultural rhetoric of prayer: on his writings inspired by the Chinese "prayer text" (yuanwen 願文). Issue 2 (3rd July 2021) - Williams, Nicholas Morrow
ABSTRACT: The religious and philosophical import of Kūkai's 空海 (774–835) writings has sometimes distracted attention away from their formal and rhetorical properties, even though these are in fact integral to their messages. This article examines Kūkai's achievement in the genre of the 'prayer text' (Ch. yuanwen 願文; J. ganmon ; K. wonmun ), which already had a convoluted history throughout Asia in the preceding centuries. Originating at the courts of Southern Dynasties China, the form is widely represented among the anonymous texts of Dunhuang, and then regained vitality in Nara and Heian Japan. Yamanoue no Okura 山上憶良 (660–733?) seems to have adapted the rhetoric of Chinese prayer texts in his own writings, and Kūkai 空海 (774–835) and Sugawara no Michizane 菅原道真 (845–903) both wrote dozens of prayer texts. Though some of Kūkai's pieces are conventional, others deploy his vast erudition in both Chinese literature and Esoteric sutras to powerful effect, enacting the triumph over death through the requisite mantras and assistance of the Mahāvairocana Buddha.